Sodium silicate gel as a precursor for the in vitro nucleation and grow of a bone-like apatite coating in compact and porous polymeric structures - Oliveira, A. L. (2003)
In the present work, a new methodology to produce bioactive coatings on the surface of starch-based biodegradable polymers or other polymeric biomaterials is proposed. A sodium silicate gel is employed as an alternative nucleating agent to the more typical bioactive glasses for inducing the formation of a calcium-phosphate (Ca-P) layer. The method has the advantage of being able to coat efficiently both compact materials and porous 3D architectures aimed at being used on tissue replacement applications and as tissue engineering scaffolds. By means of this treatment, it is possible to observe the formation of an apatite-like layer, only after 6 hours of simulated body fluid immersion. For the porous materials, this layer could also be observed inside the pores, clearly covering the cell walls. Furthermore, an increase of the surface hydrophilicity (higher amount of polar groups in the surface) might contribute to the formation of silanol groups that also act as apatite inductors. After 30 days of SBF immersion, the apatite-like films exhibit a partially amorphous nature and the Ca/P ratios became much closer to the value attributed to hydroxyapatite (1.67). The obtained results are very promising for the development of cancellous bone replacement materials and for pre-calcifying bone tissue engineering scaffolds.